Heart rate variability in arterial hypertension - S. M. Kakhramanova; A. B. Bakhshaliev; N. S. Nasrullaev (Кардиоваскулярная терапия и профилактика, 1970)
This review discusses the mechanisms of heart rate and blood pressure regulation in healthy people and patients with arterial hypertension. The role of time and spectral parameters of heart rate variability (HRV) in the assessment of autonomic status of these patients, especially during orthostatic test, is described. The paper also contains the results of the studies investigating antihypertensive medications’ effects on HRV structure.